Septic Cavernous Sinus Thrombosis (CST) with Blindness Caused by Odontogenic Infection – A Case Report - Putri Permata Valentine; Yudhi Adrianto; Sita Setyowatie (Magna Neurologica, 2023)
Introduction: Septic cavernous sinus thrombosis (CST) is a rare thrombosis, but severe, causing damage to all nerves inside the cavernous sinus. The incidence rate of CST is estimated at two to four per million people per year. The symptom usually varies, gradually worsening, making diagnosis harder and potentially making permanent disability. Early detection and prompt treatment are very important to lower the morbidity rate. Case: Tn. M had complained of multiple headaches attacks since 8 months ago before being admitted followed by diplopia. Complaints had worsened 3 months before with the loss of vision in the left eye. MRI showed left thrombosis sinus cavernous. The terrible headache was scaled 8-9 with VAS score. The patient’s left eye was found proptosis palpebra, with anisocoria and mydriasis followed by no direct light reflex also indirect light reflex, visual acuity of the left eye is no light response, whereas the patient’s right eye is normal. On the patient’s left eye was found gaze palsy sinistra. The abnormal blood result was leucocytosis and thrombocytosis. The patient was given fondaparinux once a day with a dose of 6000 units subcutaneously for 5 days. After that, the headache was decreased significantly. The patient underwent 5 tooth extraction done by mouth surgeon after being discharged. The patient was given 20 mg rivaroxaban per day for three weeks, then 10mg per day for three months, and evaluated with MRV again. Conclusion: CST is still very rare but very lethal and makes permanent disability on the patient. Through this case, we demonstrate the potential of tooth infection which leads to septic CST and caused ophthalmoplegia and blindness.